Роль арт-терапевтических практик в коррекции детско-родительских отношений, в семьях воспитывающих детей с ДЦП - Иевлева, Ольга (CEP USM, 2023)
Статья посвящена исследованию роли арт-терапевтических практик в улучшении взаимодействия родителей, воспитывающих детей с детским церебральным параличом со своими детьми. Основное внимание в работе автор акцентирует на том, что арт-терапия является эффективным методом работы с родителями детей с ДЦП, которая позволяет выразить эмоции и чувства через творчество. В статье рассматривается влияние арт-терапевтических практик в педагогическом взаимодействии педагога и родителей, воспитывающих детей с детским церебральным параличом. В материале представлены результаты реализации педагогической деятельности по преодолению нарушений детско-родительских отношений в семьях, воспитывающих детей с ДЦП; уделено внимание включению практик арт-терапии в совместную деятельность специалистов и родителей. Результаты исследования подтверждают эффективность использования арт-терапии в преодолении нарушений детско-родительских отношений при воспитании детей с ДЦП. Арт-терапевтические практики могут помочь педагогам снизить райдер родительских ожиданий, помочь родителям экологично принять особенности своих детей и в целом стабилизировать эмоциональный фон в семье. Работа имеет междисциплинарный характер, написана на стыке специальной педагогики и специальной психологии. Статья будет интересна специалистам в области специальной педагогики, специальной психологии.

The article is devoted to the study of the role of art therapeutic practices in improving the interaction of parents raising children with cerebral palsy with their children. The author focuses his work on the fact that art therapy is an effective method of working with parents of children with cerebral palsy, which allows them to express emotions and feelings through creativity. The article examines the influence of art therapeutic practices in the pedagogical interaction between a teacher and parents raising children with cerebral palsy. The material presents the results of the implementation of pedagogical activities to overcome violations of parent-child relationships in families raising children with cerebral palsy; Attention is paid to the inclusion of art therapy practices in the joint activities of specialists and parents. The results of the study confirm the effectiveness of the use of art therapy in overcoming violations of parent-child relationships when raising children with cerebral palsy. Art therapeutic practices can help teachers reduce parental expectations, help parents accept the characteristics of their children in an environmentally friendly manner, and generally stabilize the emotional background in the family. The work is interdisciplinary in nature, written at the intersection of special pedagogy and special psychology. The article will be of interest to specialists in the field of special pedagogy and special psychology.
The role of art therapeutic practices in the pedagogical interaction of the teacher and parents educing children with ICP
Keywords: детство; детско-родительские отношения; детский церебральный паралич; семья; педагогическое сопровождение; арт-терапия; художественные практики; childhood; child-parent relations; cerebral palsy; family; pedagogical support; art therapy; artistic practices